The Use Of Tangram Media To Improve Mathematics Learning Outcomes In 1st Grade Elemtary School Students - Wulandari, Anita (Universitas Sebelas Maret, 2022)
Learning media is something that is very necessary in every lesson. Learning media supports the achievement of the learning objectives themselves, especially the use of concrete media in class 1 students on geometry material. Mathematics learning geometry phase A class 1 found problems regarding the material for compiling (composing) and breaking down (decomposing) flat shapes, namely the lack of concrete media that supports learning geometry on this material so that students' understanding is still not optimal. Based on these problems, the researcher conducted research on the use of tangram media, with the aim of knowing the learning outcomes of students in composing (composing) and decomposing (decomposing) flat shapes. The method used in this research is descriptive qualitative method with data collection techniques namely observation and evaluation results of students. The learning outcomes data obtained by students is an average of 78.8 with the highest score of 100 and the lowest score of 40. Based on the results of these data it can be said that the ability of students in compiling (composing) and decomposing (decomposing) flat shapes is still very varied so that further use of tangram media is needed to further improve student learning outcomes.